H-bonding in entrapped water in poly(o-methoxyaniline): Results from a differential scanning calorimetry study - De Souza, N. C.; Silva, JR; Giacometti, J. A.; Oliveira, O. N. (Elsevier B.V., 2006)
Differential scanning calorimetry (DSC) was used to investigate entrapped water in poly(o-methoxyaniline) (POMA) in powder form. Two endothermic peaks were attributed to removal of water molecules that were adsorbed with distinct energies. By obtaining thermograms at various heating rates, we succeeded in applying Kissinger's approaches to estimate activation energies for the water adsorbed. The values obtained were ca. 25 and 53 kJ/mol, which correspond to H-bonding interactions, probably at the amine and imine centers of POMA, respectively. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: poly(o-methoxyaniline); H-bonding; entrapped water; differential scanning calorimetry